Spatial-temporal patterning of Ca(2+) signals by the subcellular distribution of IP(3) and IP(3) receptors - Lock, Jeffrey T. (Semin Cell Dev Biol, 2019)
The patterning of cytosolic Ca(2+) signals in space and time underlies their ubiquitous ability to specifically regulate numerous cellular processes. Signals mediated by liberation of Ca(2+) sequestered in the endoplasmic reticulum (ER) through inositol trisphosphate receptor (IP(3)R) channels constitute a hierarchy of events; ranging from openings of individual IP(3) channels, through the concerted openings of several clustered IP(3)Rs to generate local Ca(2+) puffs, to global Ca(2+) waves and oscillations that engulf the entire cell. Here, we review recent progress in elucidating how this hierarchy is shaped by an interplay between the functional gating properties of IP(3)Rs and their spatial distribution within the cell. We focus in particular on the subset of IP(3)Rs that are organized in stationary clusters and are endowed with the ability to preferentially liberate Ca(2+).